(untitled) (Texas Journal of Medical Science, 2023)
This article explores the morphological alterations in blood vessels within various organs in individuals with diabetes mellitus. Diabetes mellitus, a chronic metabolic disorder, exerts a profound impact on vascular health, resulting in structural changes that contribute to a range of complications. Through a comprehensive review of existing literature and histological studies, this article delves into the diverse manifestations of vascular morphological changes in organs such as the heart, kidneys, eyes, and peripheral tissues. Understanding these alterations is crucial for elucidating the pathophysiological mechanisms underlying diabetic complications and developing targeted therapeutic strategies to mitigate their effects.